2020
DOI: 10.1371/journal.pone.0228440
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of home delivery in Nepal – A disaggregated analysis of marginalised and non-marginalised women from the 2016 Nepal Demographic and Health Survey

Abstract: Conclusion We conclude that poor education, poor economic status, non-completion of four ANC visits and belonging to Province 2 particularly determined either group of women to deliver at home, whereas residing in rural areas, living far from health facility, and belonging to Province 7 determined marginalised women to deliver at home. Preventing mothers from delivering at home would thus require focusing on specific geographical areas besides considering wider socioeconomic determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 35 publications
16
44
0
Order By: Relevance
“…Women who had access to health facilities were more likely to utilize institutional delivery service. This finding is in line with studies [ 18 , 28 , 29 ]. This could be explained by an increased distance from the health facility, transport cost, and lost production time, as well as possible lower exposure to health information.…”
Section: Discussionsupporting
confidence: 94%
“…Women who had access to health facilities were more likely to utilize institutional delivery service. This finding is in line with studies [ 18 , 28 , 29 ]. This could be explained by an increased distance from the health facility, transport cost, and lost production time, as well as possible lower exposure to health information.…”
Section: Discussionsupporting
confidence: 94%
“…Muslim women were more likely to deliver at home in this study, compared to women who belonged to other religions. Similar to the findings of this study, a study in Nepal, identified that Muslim women were more likely to deliver at home compared to women of other religions [ 33 ]. A study in Ghana also identified low utilization of maternal healthcare skilled service among Muslim women [ 56 ].…”
Section: Discussionsupporting
confidence: 87%
“…These findings could be explained by older women or health personnel placing greater emphasis on the benefits of childbirth in health facilities by skilled health personnel due to the increased risk of complications due to the mother's older age. However, a study in Nepal reported that older pregnant women had a higher probability of home births given the association between higher maternal age with multiparity and precipitous childbirth [ 36 ]. Nonetheless, in our study, women in the age group of young adolescents presented the highest probability of having a home birth.…”
Section: Discussionmentioning
confidence: 99%